Percursos formativos das mulheres líderes comunitárias em São Luís - TEIXEIRA, Antonieta Lago (2019)
Women's history of action along the way has been segregated, invisible, and left behind, although they are always in the trenches of social struggles, and more recently in community movements. From this point of view, there is an interest in this research that aims to analyze and reveal how the formative pathways and their influence on the identity construction of women community leaders in the Municipality of, being a woman in the exercise of community leadership. In order to do so, we reflect on the concepts of identity and the category of course to lead us to understand the formative paths and how these intervene in the identity construction of these women, in addition to the performance and exercise of female leadership, passing through their trajectory and the various aspects of life personal and collective. We turn to studies that address the historical course of social movements and the community movement, in addition to the involvement of women in front of these movements and their feminine protagonism. Regarding the academic aspects, this study is included Area of Concentration: Diversity, Culture and Social Inclusion, whose Research Line is: Education, Women and Gender Relations - of the GEMGE Research Group. Thus, we define that as far as its approach this research is qualitative of the Auto biographical type, considering that it will bring the trajectory of life of the women from the studies raised, enabling them to Speak of the I through the research. Its starting point is not intentionality, but it develops spontaneously, giving rise and making visible to this woman who leads other people, other women and linked to this trajectory, the processes of her formative pathway, which becomes meaningful and constructive, meaning in the performance of these women to exercise leadership.